Bahir Dar Child Development Cross-Sectional Study, Ethiopia: study protocol - Alemayehu Worku; Yemane Berhane; Lian V Folger; Anne CC Lee; Krysten North; Nebiyou Fasil; Kalkidan Yibeltal; Fred Van Dyk; Firehiwot Workneh; Theresa I Chin; Sarah K G Jensen; Unmesha Roy Paladhi; et al. (BMJ Paediatrics Open)
Introduction Foundational preacademic skills are crucial for academic success and serve as predictors of socioeconomic status, income and access to healthcare. However, there is a gap in our understanding of neurodevelopmental patterns underlying preacademic skills in children across low-income and middle-income countries (LMICs). It is essential to identify primary global and regional factors that drive children’s neurodevelopment in LMICs. This study aims to characterise the typical development of healthy children and factors that influence child development in Bahir Dar, Ethiopia.Methods and analysis The Bahir Dar Child Development Study is a cross-sectional study implemented in two health centres, Shimbit and Abaymado and in Felege Hiwot Comprehensive Specialized Hospital (FHCSH) in Bahir Dar, Amhara, Ethiopia. Healthy children between 6 and 60 months of age will be recruited from the health centres during vaccination visits or via community outreach. Young children aged 6–36 months will complete the Global Scale for Early Development. A battery of paper and tablet-based assessments of neurocognitive outcomes including visual and verbal reasoning, executive functions and school readiness will be completed for children aged 48–60 months. Caregivers will respond to surveys covering sociodemographic information, the child’s medical history and nutrition, and psychosocial experiences including parental stress and mental health. During a second visit, participants will undergo a low-field MRI scan using the ultra-low-field point-of-care Hyperfine MRI machine at FHCSH. Analyses will examine relationships between risk and protective factors, brain volumes and neurocognitive/developmental outcomes.Ethics and dissemination The study is approved by the Institutional Review Boards of Addis Continental Institute of Public Health (ACIPH/lRERC/004/2023/Al/05-2024), Mass General Brigham Hospital (2022P002539) and Brown University (STUDY00000474). Findings will be disseminated via local dissemination events, international conferences and publications.Trial Registeration number NCT06648863.